GCMS analysis of sadagura (smokeless tobacco), its enhanced genomic instability causing potential due to arsenic co-exposure, and vitamin-C supplementation as a possible remedial measure: a study involving multiple model test systems. (2nd January 2022) - Das, Samrat; Upadhaya, Puja; Barhoi, Dharmeswar; Nath Barbhuiya, Sweety; Langthasa, Pimily; Giri, Sarbani
Abstract: North-eastern states of India, including Assam, have a high prevalence of head and neck cancer cases. In these regions, Sadagura is a unique form of smokeless tobacco (SLT). There are fewer reports regarding the effects of simultaneous sadagura and arsenic co-exposure. Analysis of chemical compounds present in sadagura aqueous extract was done using gas chromatography–mass spectrometry. Estimation of arsenic contamination in groundwater and bioaccumulation in human tissues was performed by using atomic absorption spectroscopy. Buccal micronucleus cytome (BMCyt) assay and analysis of various peripheral blood parameters were performed among study volunteers. Chronic exposure (90 days) experiments were performed in mice test system in vivo to determine any possible protective potential of vitamin C (Vit-C) supplementation against sadagura and arsenic co-exposure. BMCyt assay results revealed a higher incidence of micronucleated cells ( p  < 0.001), and cell death biomarker among sadagura consumers residing in arsenic affected areas. Comet assay of mice femur bone marrow cells following chronic exposure of the test substances revealed a reduction in DNA damage due to Vit-C supplementation. Histological examination of the hepatic and renal tissues revealed marked improvement due to Vit-C supplementation in mice against sadagura and arsenic chronic co-exposure. Indiscriminate consumption, presence of various harmful compounds in sadagura along with arsenic co-exposure might be a vital link for the higher incidence of oral cancer in the region. Chronic Vit-C supplementation study results in mice show its effective remedial potential against combined sadagura and arsenic co-mediated genotoxicity and ultrastructural changes in major organs.